2020
DOI: 10.3390/cells9020324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cancer Stem Cell Subpopulations in Head and Neck Metastatic Malignant Melanoma

Abstract: Cancer stem cells (CSCs) have been identified in many cancer types. This study identified and characterized CSCs in head and neck metastatic malignant melanoma (HNmMM) to regional lymph nodes using induced pluripotent stem cell (iPSC) markers. Immunohistochemical (IHC) staining performed on 20 HNmMM tissue samples demonstrated expression of iPSC markers OCT4, SOX2, KLF4, and c-MYC in all samples, while NANOG was expressed at low levels in two samples. Immunofluorescence (IF) staining demonstrated an OCT4+/SOX2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Three out of four primary cell lines derived from four different HNmMM tissue samples formed tumorspheres in vitro. As with the current study of mHNcSCC, the formation of tumorspheres in HNmMM-derived primary cell lines in vitro, provides preliminary functional evidence of the presence of CSCs in HNmMM tissues (44).…”
Section: Discussionsupporting
confidence: 53%
“…Three out of four primary cell lines derived from four different HNmMM tissue samples formed tumorspheres in vitro. As with the current study of mHNcSCC, the formation of tumorspheres in HNmMM-derived primary cell lines in vitro, provides preliminary functional evidence of the presence of CSCs in HNmMM tissues (44).…”
Section: Discussionsupporting
confidence: 53%
“…CSCs have been identified in many cancer types, including OCSCC of different subsites, 9 11 glioblastoma, 12 renal clear cell carcinoma, 13 primary 14 and metastatic 15 colon adenocarcinoma, and metastatic malignant melanoma. 16 , 17 We have recently reported the presence of 4 CSC subpopulations within human MDHNcSCC: an OCT4 + /NANOG + /SOX2 + /KLF4 + /c-MYC + subpopulation within the TNs, the PTS, the endothelium of the microvessels within the PTS, and an OCT4 + /NANOG − /SOX2 + /KLF4 + /c-MYC + subpopulation solely within the PTS. 27 These CSCs have been suggested as a novel therapeutic target 5 by modulating the RAS.…”
Section: Discussionmentioning
confidence: 96%
“…CSCs have been identified in many cancer types, including oral cavity SCC (OCSCC) of different subsites, 9 11 glioblastoma, 12 renal clear cell carcinoma, 13 primary 14 and metastatic 15 colon adenocarcinoma, and metastatic malignant melanoma. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Although our approach is theoretical, there is recent evidence of an invariant stem cell hierarchy in glioblastoma tumors giving rise to progenitor cells with an extensive self-maintenance capacity [22,31]. There is also evidence of subpopulations of cells showing a differential expression of embryonic stem cell markers in head and neck squamous cell carcinoma, colon adenocarcinoma, melanoma, and buccal squamous cell carcinoma [23,[33][34][35], in addition to evidence that more differentiated cells can generate tumors [9,10,17,25,28]. Moreover, recent findings on antibody-drug conjugates (ADC) showed that the targeting of Lgr5(+) colon CSCs with an ADC controlled the disease, but did not eliminate it, as observed in their reported growth curves [52].…”
Section: Discussionmentioning
confidence: 99%
“…This idea has been put forward elsewhere [16]. Although recent reports [31][32][33][34][35] mention the existence of different populations of cancer cells differentially expressing embryonal stem cell markers at the mRNA and protein level, confirmation of their stemness potential and whether they belong to the same hierarchical structure were not tested. In addition to this complexity, Liu et al postulated that CSCs can shift between two different stem-like states [36].…”
Section: Hypothesismentioning
confidence: 99%